2019
DOI: 10.1155/2019/6936042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of LASEK for High Myopia Correction between the Triple-A Profile and the Zyoptix Tissue Saving Profile

Abstract: Purpose. To compare the effects of correcting high myopia using the MEL®90 Triple-A profile LASEK at a 500 Hz pulse rate (Triple-A group) versus the Zyoptix tissue-saving ablations of Technolas 217z laser platform at 100 Hz (TS group). Methods. This retrospective study included 50 eyes in the Triple-A group and 42 eyes in the TS group with manifest refraction spherical equivalent (MRSE) of −6 diopters (D) to −10 D. We compared uncorrected distance visual acuity, MRSE, corrected distance visual acuity, and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Our findings partly confirmed those of Yu et al who reported no difference in visual outcomes after SMILE and LASEK for low-to-moderate myopia at 3 months postoperatively [28]. Our previously published studies also proved the safety and stability of LASEK for the correction of mild, moderate, and high myopia [29,30]. However, SMILE became a superior choice over LASEK in terms of lesser intensity of postoperative pain.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings partly confirmed those of Yu et al who reported no difference in visual outcomes after SMILE and LASEK for low-to-moderate myopia at 3 months postoperatively [28]. Our previously published studies also proved the safety and stability of LASEK for the correction of mild, moderate, and high myopia [29,30]. However, SMILE became a superior choice over LASEK in terms of lesser intensity of postoperative pain.…”
Section: Discussionsupporting
confidence: 90%